TINJAUAN FIQH SIYASAH DUSTURIYAH DAN UNDANG-UNDANG NOMOR 18 TAHUN 2019 TERHADAP IMPLEMENTASI PENGEMBANGAN KURIKULUM DI MADRASAH IBTIDAIYAH AL-ZAYTUN - Jaziroh, Wardah; Rahim, Abdur; Sajali, Munawir (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research is motivated by changes in the national education system and global challenges that have forced Islamic educational institutions, particularly the Al-Zaytun Elementary Madrasah, to update their curriculum without losing their religious focus. As part of a pesantren-based educational institution, the Al-Zaytun Elementary Madrasah has been in the spotlight for integrating the national curriculum with Islamic values within a unique environment, namely a boarding school-based Islamic boarding school. This study describes a qualitative approach with a case study research type. The data collection method uses interview methods, and documentation. The technique is by examining data, classification, and conclusions. The data analysis model used is a qualitative descriptive method using an inductive thinking process. While the data validity test used in this study is a credibility test with the triangulation method. The results of this study indicate that the Implementation of Curriculum Development at Al-Zaytun Elementary Madrasah in the Review of Fiqh Siyasah Dusturiyah is the Islamic state administration Fiqh rules used in this thesis as an analytical framework to assess the extent to which state education policies are in line with Islamic principles in governance and public policy management. In this context, the curriculum is not only seen as an educational instrument, but also as a concrete form of policy implementation that has an impact on the formation of character and thinking of future generations. A review of Law Number 18 of 2019 on the Implementation of Curriculum Development at Al-Zaytun Elementary Madrasah shows that the implementation of the Independent Curriculum as a development of the 2013 Curriculum through the Decree of the Minister of Religious Affairs of the Republic of Indonesia No. 450 of 2024 concerning Guidelines for the Implementation of the Independent Curriculum, has been successfully integrated well. This policy not only complies with applicable legal provisions, but also ensures that the curriculum at Madrasah Ibtidaiyah Al-Zaytun remains relevant to current developments while maintaining Islamic values.